Rational Foundations of National Self-Organization in the Constitutional Law of the Islamic Republic of Iran - Ali Abolfazli (دانش حقوق عمومی)
The term "self-organization," which is a rational principle, in this article refers to the structuring of social relationships among humans through the limitation of will and adherence to the resulting obligations. On the other hand, the foundations of national self-organization in the constitutional law of the Islamic Republic of Iran, such as sovereignty, which represents the superior power of command in the political community, and the central position of power, which are essential elements in various political and legal domains, as well as freedom, which is a fundamental component in determining collective destiny, all these foundations are realized based on this principle. The question arises: What are the rational foundations of national self-organization in the constitutional law of the Islamic Republic of Iran? The present research employs a descriptive-analytical method to examine the concept and implications of this principle and its relation to the rational foundations of national self-organization in constitutional law. The results of the research indicate that, according to the rational foundations of national self-organization in constitutional law, the exercise of sovereignty, which provides the groundwork for human social life within the framework of law, order, and political organization, is necessary. Given that human nature tends toward domination and despotism, and power facilitates this tendency, measures must be taken to prevent despotism and control power through internal and external tools. Additionally, freedom, coupled with human responsibility and its manifestation in social life, will be organized based on this principle.